The Natural History of Bats on Mt. Makiling, Luzon Island, Philippines - Ingle, Nina R. (Silliman Journal, 2024)
Over 1500 bats representing 20 species were captured in lowland forest on Mt. Makiling, Luzon Island, from January to August 1989. The two most commonly captured species, the fruit bats Ptenochirus jagori and Cynopterus brachyotis, were found to reproduce seasonally with two birth periods per year. Although micro-chiropterans comprised only 8% of all captures, they represented 14 species. Species accounts presented here include information on reproduction, habitat use, and other aspects of natural history.